John Montgomery Cooper: A Memoir - Sloyan, Gerard Stephen (American catholic studies, 2009)
The remarkable life of Monsignor John Montgomery Cooper (1881-1949), a neglected figure in American Catholic history, who embodied the ideal of the diocesan priest academic, is warmly recalled by one who was briefly his student and later his successor at The Catholic University of America. Cooper's influence in shaping, decades of religious instruction for undergraduates is recalled in detail, and his scholarly stature as an anthropologist is duly noted.